PENGARUH VARIASI LATIHAN TERHADAP KETERAMPILAN PASSING DALAM PERMAINAN SEPAK BOLA DI EKSTRAKURIKULER SMPN 3 PONTIANAK - Likardi Likardi; Andika Triansyah; Mimi Haetami (Universitas Tanjungpura, 2019)
Abstract:The problem in this study was whether there was an effect of variations in training on passing skills in the game ed football at extracurricular Pontianak 3 Public High School. This study aims to determine the effect of variations in training on the passing skills of football extracurricular students at Pontianak Junior High School 3.The method in this study used an experimental method with the form of pre-experimental design. The population in this study were 28 extracurricular students of Pontianak Junior High School 3 in Pontianak. The number of samples in this study was 28 students. The instrument used was the kick test column. Data analysis using t test analysis (influence test).Based on the calculation of the data obtained by using the ball test, count test, T count equal to 3.28 and T table equal to 2.052 can be concluded t count> t table (3.28> 2.052). Thus was, there was a significant effect on variations in foodball practice on the ball passing skills of extracurricular students at Pontianak Middle School 3. Moderate percentages was higher than those given variations in passing exercise by 44%.Keywords: Variation of training, Passing, football